2020
DOI: 10.21203/rs.2.22890/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The correlation between vitamin D and maternal/infant outcomes, inflammatory response in pregnant women

Abstract: Purposes To analyze the effects of vitamin D deficiency in pregnant women on common adverse pregnancy outcomes and small for gestational age (SGA) and to detect the expression of inflammatory factors in pregnant women to provide a theoretical basis for the treatment of vitamin D deficiency in pregnant women. Methods Serum samples from pregnant women from January 2015 to December 2015 were collected to measure the 25-(OH)D level. The effects of maternal age, pregnancy, season, parity and temperature on vitamin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Traditional Chinese medicine believes that the main pathogenesis of KOA is liver and kidney deficiency, blood stasis and dampness. In combination with modern medicine, it has been found that obstructed blood circulation can lead to an increase in thrombin and coagulation factor complexes in the blood, thereby stimulating the synthesis and release of inflammatory factors by the vascular endothelium [18][19] . The results of this experiment showed that the content of apoptotic protein Bax and Caspase-3 decreased after treatment with Bushen Huoxue Tang, indicating that Bushen Huoxue Tang treatment can inhibit cell apoptosis, and the inflammatory factor IL-1 β, TNF-α, The iNOS level was significantly reduced, and the HE staining results combined with the Mankin score were lower, indicating that the treatment of Bushen Huoxue Tang effectively alleviated inflammatory infiltration and cell apoptosis [20] .…”
Section: Discussionmentioning
confidence: 99%
“…Traditional Chinese medicine believes that the main pathogenesis of KOA is liver and kidney deficiency, blood stasis and dampness. In combination with modern medicine, it has been found that obstructed blood circulation can lead to an increase in thrombin and coagulation factor complexes in the blood, thereby stimulating the synthesis and release of inflammatory factors by the vascular endothelium [18][19] . The results of this experiment showed that the content of apoptotic protein Bax and Caspase-3 decreased after treatment with Bushen Huoxue Tang, indicating that Bushen Huoxue Tang treatment can inhibit cell apoptosis, and the inflammatory factor IL-1 β, TNF-α, The iNOS level was significantly reduced, and the HE staining results combined with the Mankin score were lower, indicating that the treatment of Bushen Huoxue Tang effectively alleviated inflammatory infiltration and cell apoptosis [20] .…”
Section: Discussionmentioning
confidence: 99%